Academic and Psychosocial Adaptation and its Association with Identity Levels and Some Background Variables of An-Najah National University Students - Yousef, Ala' Ibraheem (Journal of Educational and Psychological Sciences, 2021)
This study aims at recognizing the level of social and psychological adaptation and its connection with the students of An-Najah National University in Nablus governorate in light of the background variables. Also, it seeks to clarify the correlational relations between social, psychological and academic adaptation and identity ranks. In order to achieve the aims of the study, a sample of (280) students from An-Najah National University is chosen. The consistency and validity of the tools of the study are verified. Results have shown their validity as it follows the correlational and descriptive methods. The following are the results of the study: 1- There are positive statistical relations between psychological and social adaptation and identity ranks of stopping, closure and dispersion. However, there isn’t any statistical relation between identity achievement and social and psychological adaptation. 2- There are statistical differences in the ranks of identity of the variable of scholastic year or place of residence or economic level. Besides, there are statistical differences in the averages of identity stopping and closure due to the variable of scholastic year. 3- There are differences in the average of stopping identity in the first year and the second, third and fourth year students in favor of the first year students. The source of the differences in the average of identity closure is between the first year students and the second and third year students in favor of the first year students. 4- There are statistical differences in the averages of achieving closure identity due to place of residence that the differences in the averages of achieving identity among camp citizens in the cities and villages in favor of camps citizens due to closing their identity between the citizens of the cities and villages in favor of the dwellers of the village. 5- There are statistical differences in the averages in the ranks of identity due to the economic level. Also, there are statistical differences among the averages of the social and psychological adaptation due to the variable of the scholastic year that they are between the first year students and the second and third year students in favor of the first year students. 6- All the hypotheses of the study are refuted except for two, namely: there are statistical differences in the rank of identity due to the variables of scholastic year and place of residence. The second is that there are statistical differences in the social and psychological adaptation due to the variable of scholastic year. In light of these results, the researcher recommends offering guidance programs highlighting ranks of the identity of students for its positive and effective impact in achieving their goals and changing their course of life by achieving their psychological, social and academic adaptation.